An interior-point algorithm for P∗(κ)-LCP based on a new trigonometric kernel function with a double barrier term - Li, Xin; Zhang, Mingwang; Chen, Yan (Journal of applied mathematics & computing, 2017)
In this paper, we present a new large-update interior-point algorithm for P ∗ ( κ ) -linear complementarity problem. The new algorithm is based on a trigonometric kernel function which differs from the existing kernel functions in which it has a double barrier term. By a simple analysis, we show that the new algorithm enjoys O ( ( 1 + 2 κ ) n 2 3 log n ε ) iteration complexity. This complexity estimate improves a result from El Ghami et al. (Optim Theory Decis Mak Oper Res Appl 31: 331–349, 2013 ) and matches the currently best known complexity result for P ∗ ( κ ) -linear complementarity problem based on trigonometric kernel functions.